PERKEMBANGAN SUKA MAKMUE MENJADI PUSAT PEMERINTAHAN KABUPATEN NAGAN RAYA 2002-2016 - Zulhasmi .; Husaini .; Zainal Abidin (Universitas Syiah Kuala, 2018)
ABSTRACTSuka Makmue is a city center of kabupaten Nagan Raya. The existence of this central government is far from the center of public activity. Suka Makmue Development has been pioneered since 2002 until now and currently the location of suka Makmue already has a variety of infrastructure buildings, especially offices as the venue of government activities Nagan Raya District.The reasearh with title Development of suka makmue as a kabupaten Nagan raya goverment center 2002-2016, which aim to 1) describes the development of infrastructural facilities and infrastructure of suka Makmue to Become the Central Government of kabupaten Nagan Raya, 2006-2016, and 2) to analyze the factors that prevent the development of suka Makmue Becoming the Government Center of kabupaten Nagan Raya , 2006-2016This research uses qualitative approach and historical method, which has the step of theme selection, heuristic, verification, interpretation and historiography. Technique of collecting data is done by interview, documentation, observation and literature study.Based on the results of the research note that 1) development of Suka Makmue infrastructure, kabupaten Nagan Raya , 2002-2016 in terms of physical infrastructure and non-physical starts since 2006 and continues to be sustainable every year. The development was mainly seen in the main office such as: the Bupati's office, the DPRK office, the education office, and others. Non-physical suka Makmue Development is seen in the number of employee. Since 2002-2016 the number of civil servants in Suka Makmue reached 922 people, each consisting of 638 male employees and 284 female employees, and 2) factors that inhibit the development of suka Makmue,2002-2016 because of the frequent change of head department or high officials, so that the development program that has been designed can notbe fully realized and community factors that do not agree about the land they own are bought by the government at a low price.Keywords:development, suka makmue, goverment center. ABSTRAKSuka Makmue merupakan sebuah pusat kota dari Kabupaten Nagan Raya. Keberadaan lokasi pusat pemerintahan ini jauh dari pusat keramain masyarakat. Pembangunan Suka Makmue sudah dirintis sejak tahun 2002 dan hingga saat ini lokasi Suka Makmue sudah terdapat berbagai bangunan infrastrukur terutama perkantoran sebagai tempat berlangsungnya kegiatan pemerintahan Kabupaten Nagan Raya. Penelitian yang berjudul “Perkembangan Suka Makmue Menjadi Pusat Pemerintahan Kabupaten Nagan Raya 2002-2016”, yang bertujuan untuk (1) mendeskripsikan perkembangan sarana dan prasarana infrastruktur Suka Makmue Menjadi Pusat Pemerintahan Kabupaten Nagan Raya, 2002-2016, dan (2) menganalisis faktor-faktor yang menghambat perkembangan Suka Makmue Menjadi Pusat Pemerintahan Kabupaten Nagan Raya, 2002-2016.Penelitian ini menggunakan pendekatan kualitatif dan metode sejarah, yang memiliki langkah pemilihan tema, heuristik, verifikasi, interpretasi dan historiografi. Teknik pengumpulan data dilakukan dengan wawancara, dokumentasi, observasi dan studi pustaka.Berdasarkan hasil penelitian diketahui bahwa (1) perkembangan infrastruktur Suka Makmue, Kabupaten Nagan Raya, 2002-2016 dari segi fisik infrastruktur dan non fisik dimulai sejak tahun 2006 dan terus bersifat berkelanjutan setiap tahunnya. Pembangunan itu terutama terlihat pada kantor utama seperti: kantor bupati, kantor DPRK, kantor dinas pendidikan, dan lain-lain. Pengembangan Suka Makmue yang bersifat non fisik terlihat pada jumlah kepegawaian. Sejak 2002-2016 jumlah kepegawaian PNS di Suka Makmue mencapai 922 jiwa yang masing-masing terdiri dari 638 jiwa pegawai laki-laki dan 284 jiwa pegawai perempuan, dan (2) faktor yang menghambat perkembangan Suka Makmue, 2002-2016 karena faktor sering terjadinya gonta-ganti kepala dinas atau pejabat-pejabat tinggi, sehingga program pembangunan yang sudah dirancang tidak dapat terealisasikan sepenuhnya dan faktor masyarakat yang tidak setuju lahan yang mereka miliki dibeli oleh pemerintah dengan harga murah. Kata Kunci: Perkembangan, Suka Makmue, Pusat Pemerintahan.